A Dynamic Model of Optimal Creditor Dispersion. (13th October 2020) - ZHONG, HONGDA
ABSTRACT: Borrowing from multiple creditors exposes firms to rollover risk due to coordination problems among creditors, but it also improves firms' repayment incentives, thereby increasing pledgeability. Based on this trade‐off, I develop a dynamic debt rollover model to analyze the evolution of creditor dispersion. Consistent with empirical evidence, I find that firms optimally increase creditor dispersion after poor performance. In contrast, cross‐sectionally higher‐growth firms can support more dispersed creditors. Frequent debt renegotiation limits firms' ability to increase pledgeability by having more creditors. Finally, holding a cash balance while borrowing from multiple creditors improves firms' repayment incentives uniformly across all future states.